An outcome evaluation of Living Through Learning's Coronation Reading Adventure Room Programme - Zuma, Mlungisi (Institute for Monitoring and Evaluation, 2017)
This dissertation was an outcome evaluation of the Living Through Learning's Coronation Reading Adventure Room Programme. LTL's reading programme objectives include aspects of improving and developing English literacy in disadvantaged schools, teaching learners how to read and write and equipping teachers with the necessary skills to teach effectively. LTL also provides facilitators to offer assistance to the teachers in order to teach effectively in overcrowded classes. The main programme beneficiaries are teachers and grade one learners. This dissertation focuses on 18 schools in disadvantaged communities in Cape Town who received the literacy programme in 2015. Two evaluation questions were formulated, for the literacy programme. The first evaluation question focused on the learners and assessed whether or not the learners who were part of the CRAR programme were better off regarding literacy performance than they were before the programme. For the teacher characteristics, the evaluation question asked if the teachers' language teaching experience, English language proficiency, teaching self-efficacy, perceptions of usefulness of the LTL materials, and usage of the reading room had any influence on the learner's performance. Secondary data provided by LTL was utilised to answer the literacy programme evaluation question. The data included test scores of grade 1 learners from 18 different schools. Primary data was used for teacher's characteristics and this was done through a questionnaire sent out to the different teachers. Data analysis methods included descriptive statistics for the learners' assessments and inferential statistics for teacher characteristics. The results showed that learners who were part of the LTL programme showed improvement in assessment scores. All schools, except one, attained the realistic NGO (60%) standard in their reading assessments. Three schools attained the high standard (85%). Furthermore, all schools attained the 50% Curriculum Assessment Policy Statements standard in the CAPS based-assessments. Therefore, it can be concluded that the LTL programme successfully aided improvement of literacy skills of the learners who were part of the programme. In an analysis of teacher's characteristics, teacher experience in literacy was the only variable that significantly predicted learner performance in literacy. However, the results must be interpreted with caution; the absence of a comparison group makes it difficult to give all credit to the LTL programme alone. At this point I simply do not know whether it was only the programme that led to the improvement in literacy scores or whether other factors had an influence, or a joint influence in combination with the literacy programme (e.g. learners started reading more in their own time as a result of the programme).